Decriminalization and Technology Integration in Juvenile Justice: Dekriminalisasi dan Integrasi Teknologi dalam Peradilan Anak - Akbar, Rizki; Widiarto, Aan Eko (Indonesian Journal of Law and Economics Review, 2024)
This normative juridical research, utilizing statutory and conceptual approaches, aims to explore future policy models for the legal protection of children within the juvenile criminal justice system in Indonesia. Acknowledging various challenges in the current system, the study emphasizes the necessity of reforming policies to ensure legal certainty and justice for minors in conflict with the law. The proposed model advocates for a 'pure decriminalization' approach, which involves removing the punishable nature of certain criminal elements committed by juvenile legal subjects. This model is complemented by a protection policy that underscores preventative measures to decrease the involvement of children in the criminal justice system. A significant emphasis is placed on integrating technology into the system to enhance efficiency and security, thereby safeguarding children's rights more effectively. Additionally, the research highlights the need for increased inter-agency and cross-sectoral cooperation within the legal structure (police, prosecutors, and courts) to create a more coordinated and holistic approach in addressing juvenile justice issues. The findings suggest that these strategic efforts can contribute significantly to the improvement of procedural law applications for children, ensuring their human rights are not violated in future legal encounters.Highlights: Pure Decriminalization Model: Emphasizes removing the punitive aspects for certain juvenile offenses, focusing on rehabilitation over punishment. Technological Advancements: Integration of technology in the juvenile justice system to enhance efficiency, security, and protection of children's rights. Enhanced Inter-agency Collaboration: Advocates for improved cooperation between legal entities for a holistic and coordinated approach to juvenile justice issues. Keywords: Juvenile Justice, Decriminalization, Legal Protection, Technology Integration, Inter-agency Cooperation